Terminus thinning drives recent acceleration of a Greenlandic lake-terminating outlet glacier - Ed Holt; Peter Nienow; Encarni Medina-Lopez (Journal of Glaciology)
Ice-contact proglacial lakes affect ice dynamics and the transition of glacier termini from land- to lake-terminating has been shown to cause ice flow acceleration. In recent decades, the number and size of Greenlandic ice-marginal lakes has increased, highlighting the need to further understand these lake-terminating ice-margins as their influence on ice sheet mass balance increases. Here, time series of satellite-derived observations of ice velocity, surface elevation, and terminus position were generated at a lake-terminating outlet glacier, Isortuarsuup Sermia, and the nearby land-terminating Kangaasarsuup Sermia in south-west Greenland. At Isortuarsuup Sermia, annual surface velocity at the terminus increased by a factor of 2.5 to 214 ± 4 m yr−1 (2013–2021), with the magnitude of this acceleration declining with distance up-glacier. Meanwhile, near-terminus surface elevation changed at a rate of −2.3 ± 1.1 m yr−1 (2012–2021). Conversely, velocity change at Kangaasarsuup Sermia was minimal, while surface elevation change was approximately half at comparable elevations (−1.2 ± 0.3 m yr−1). We attribute these dynamic differences to thinning at Isortuarsuup Sermia and subsequent retreat from a stabilising sublacustrine moraine, and emphasise the potential of proglacial lakes to enhance future rates of mass loss from the Greenland Ice Sheet.